Site‐specific regulation of adult neurogenesis by dietary fatty acid content, vitamin E and flight exercise in European starlings. (27th December 2013) - Hall, Zachary J.; Bauchinger, Ulf; Gerson, Alexander R.; Price, Edwin R.; Langlois, Lillie A.; Boyles, Michelle; Pierce, Barbara; McWilliams, Scott R.; Sherry, David F.; MacDougall‐Shackleton, Scott A.
Abstract Exercise is known to have a strong effect on neuroproliferation in mammals ranging from rodents to humans. Recent studies have also shown that fatty acids and other dietary supplements can cause an upregulation of neurogenesis. It is not known, however, how exercise and diet interact in their effects on adult neurogenesis. We examined neuronal recruitment in multiple telencephalic sites in adult male European starlings (Sturnus vulgaris) exposed to a factorial combination of flight exercise, dietary fatty acids and antioxidants. Experimental birds were flown in a wind tunnel following a training regime that mimicked the bird's natural flight behaviour. In addition to flight exercise, we manipulated the composition of dietary fatty acids and the level of enrichment with vitamin E, an antioxidant reported to enhance neuronal recruitment. We found that all three factors – flight exercise, fatty acid composition and vitamin E enrichment – regulate neuronal recruitment in a site‐specific manner. We also found a robust interaction between flight training and vitamin E enrichment at multiple sites of neuronal recruitment. Specifically, flight training was found to enhance neuronal recruitment across the telencephalon, but only in birds fed a diet with a low level of vitamin E. Conversely, dietary enrichment with vitamin E upregulated neuronal recruitment, but only in birds not flown in the wind tunnel. These findings indicate conserved modulation of adult neurogenesis by exercise and diet across vertebrate taxa and indicate possible therapeutic interventions in disorders characterized by reduced adult neurogenesis.